Adolescentna idiopatska skolioza - Rojc, Marina (Rehabilitacija (Ljubljana), 2021)
Adolescent idiopathic scoliosis (AIS) is the most common form of structural spinal deformities, it is diagnosed by measuring Cobb angle (CK) on posteroanterior radiograph, when CK is 10° or higher and vertebral rotation on the apex of the curve can be recognised. AIS affects between 2 % and 3 % of adolescents. It is more common in young women than in young men. Ethology of disease is unknown, nonetheless, a range of hypotheses have been proposed to explain its origin. With the general belief that AIS is a multifactorial disorder, it is likely that there is no single cause for it. Idiopathic scoliosis (IS) most commonly appears in periods of growth spurts: generally, between 6 and 24 months (infantile form), between the age of 5 and 8 years (juvenile form), and at the age of 11 to 14 years of life (adolescent form). Progression of the curve is connected with growth potential (age, menarche, Risser sign, Tanner-Whitehouse scale, Sanders scale) and curve type and size. There are many different classifications of idiopathic scoliosis which are relevant for conservative and operative treatment. In last decade many high-quality studies have been published that demonstrate the effectiveness of a multidisciplinary approach in treatment of AIS with physiotherapeutic specific scoliosis exercises.
Keywords: adolescents; fizioterapija; idiopathic scoliosis; idiopatska skolioza; najstnik; ortoza za hrbtenico; physiotherapy; rehabilitation; Scoliosis; spinal orthosis; treatment; zdravljenje